Knowledge and practices on home medication storage and disposal in Syria: a population-based, cross-sectional study - Raghad Samha; Azmi Wali; Saeed Kadri; Fatima Al-Assi; Aya Al-Khalaf; Aya Al-Deeb; Mosa Shibani; Mhd Amin Alzabibi; Walid Issa Khaddam; Shahd Al-Hayek; Data Collection Group (BMC, 2024)
Abstract Background Medications are commonly found in every household. In Syria, where healthcare infrastructure faces significant challenges, improper storage can lead to reduced medication efficacy and increased health risks. Additionally, inappropriate disposal practices pose serious environmental concerns, especially in a region already grappling with environmental degradation. This study aimed to evaluate the knowledge, and practices of Syrian individuals regarding the appropriate storage and disposal of home medications. Method A cross-sectional study was conducted from September 22 to October 20, 2023, using an online survey distributed via social media apps (WhatsApp, Facebook, and Telegram) in Syria. The questionnaire, adapted from a similar study in Saudi Arabia, was translated to Arabic using the forward-backward translation technique. A convenience sampling technique was used. Inclusion criteria were participants over eighteen with expired or unused medications at home. Descriptive statistics, Chi-square tests, and binary logistic regression analysis were performed using SPSS version 27, with statistical significance defined as p < 0.05. Results A total of 2,217 responses were analyzed, with the majority of participants being female (79%) and aged between 21-30 years (56%). The study found that 90.7% of respondents dispose of expired medications in the garbage, while 95% keep medications in their original containers. Additionally, 30% consult pharmacists for storage instructions, and 64% read storage information on medication leaflets. Logistic regression analysis revealed that males were less likely to check expiration dates before use (OR: 0.58, 95% CI: 0.40-0.84) and periodically (OR: 0.68, 95% CI: 0.54-0.85). Participants aged 31-40 years were less likely to check expiration dates periodically (OR: 0.46, 95% CI: 0.31-0.68), while those with children under six years old were more likely to do so (OR: 1.29, 95% CI: 1.01-1.67). Males were also less likely to read storage instructions (OR: 0.61, 95% CI: 0.50-0.76) but more likely to ask pharmacists about them (OR: 1.26, 95% CI: 1.01-1.57). There was no significant difference in these practices between medical professionals and the general population. Conclusion This study reveals gaps in the practices related to the storage and disposal of medications among the Syrian public. The findings suggest a need for targeted public education and awareness programs to improve these practices and reduce the associated health and environmental risks.